2009
DOI: 10.4321/s1886-36552009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pharmacist managed smoking cessation clinic on quit rates

Abstract: Objective:The purpose of this study was to quantify quit rates, determine factors predicting success, and analyze patients’ perceptions at 3 months after participation in the pharmacist-managed Smoking Cessation Group Clinic.Methods:This was a prospective, single group study that was conducted in patients that had participated in the Smoking Cessation Group Clinic at the University of Iowa Hospitals and Clinics. Clinic participants received structured group counseling covering various topics associated with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
2
9
1
2
Order By: Relevance
“…While most of the studies showed a decrease in abstinence rate over time [11][12][13][14][15] , our study demonstrated a significant increase (P<0.05) in abstinence rate from clinic completion (19.8%) to both 6-(23.8%) and 12-month (25.4%) followup. This is consistent with the results found by Philbrick and colleagues who reported an increase in abstinence rate from 47.6% to 52.4% at 3 and 6 months respectively 16 and also the pilot study performed in CGH previously 7 . The exact reasons contributing to the inconsistencies in results are not clear due to the differences in study designs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…While most of the studies showed a decrease in abstinence rate over time [11][12][13][14][15] , our study demonstrated a significant increase (P<0.05) in abstinence rate from clinic completion (19.8%) to both 6-(23.8%) and 12-month (25.4%) followup. This is consistent with the results found by Philbrick and colleagues who reported an increase in abstinence rate from 47.6% to 52.4% at 3 and 6 months respectively 16 and also the pilot study performed in CGH previously 7 . The exact reasons contributing to the inconsistencies in results are not clear due to the differences in study designs.…”
Section: Discussionsupporting
confidence: 82%
“…A meta-analysis suggested that the number of counselling sessions and treatment effectiveness is associated in a doseresponse relationship 17 . This is supported by other studies which found significant increase in abstinence rate in patients who have attended more number of sessions (P<0.05) 8,16 . Hence, we could consider initiatives to improve the turn up rate of patients as slightly more than half of the patients in this study only attended one counselling session.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This contradicted the Russell Standard (SRNT Subcommittee on Biochemical Verification, 2002) that stipulated further biochemical verification in addition to the self-reported smoking status is required. However, several studies have supported that self-verification is sufficiently valid in ascertaining smoking status (Alberg et al, 2004;Attebring, Herlitz, Berndt, Karlsson, & Hjalmarson, 2001;Philbrick et al, 2009).…”
Section: Strength and Limitationsmentioning
confidence: 98%
“…Pharmacists are uniquely positioned to simultaneously provide both smoking cessation services and SCAs to a smoker who wants to quit. A large body of research has been published, which provides evidence that pharmacists see themselves as playing a role in providing cessation support for smokers (Dent, Harris, & Noonan, 2007Dent, Scott, & Lewis, 2004;Kennedy, Giles, Chang, Small, & Edwards, 2002;Maguire, McElnay, & Drummond, 2001;Philbrick, Newkirk, Farris, McDanel, & Horner, 2009;Ragucci & Shrader, 2009;Roth & Westman, 2001;Zillich, Ryan, Adams, Yeager, & Farris, 2002). Increasing the utilisation of pharmacists in smoking cessation activities may have a positive impact on increasing quit smoking rates at population level.…”
Section: Introductionmentioning
confidence: 95%